Laser photo-detachment combined with Langmuir probe in magnetized electronegative plasma: how the probe size affects the plasma dynamic?. (3rd November 2021) - Oudini, N; Bendib, A; Agnello, R; Furno, I; Taccogna, F
Abstract: Laser photo-detachment combined with a Langmuir probe (LP) is used to diagnose negative ion properties in electronegative plasmas. The technique relies on the combined use of a laser pulse and an LP. The laser pulse converts negative ions into electron–atom pairs, while the LP tracks the temporal evolution of electron current (laser photo-detachment signal) that is analyzed to retrieve the negative ion density. Although an external magnetic field is frequently used to enhance the negative ion production and extraction, the data analysis often neglects the effects of the magnetic field on the probe current. This work investigates the response of an electronegative plasma to a laser pulse in the presence of an external magnetic field through a two-dimensional particle-in-cell/Monte Carlo collision model. The results show that a low electron density region surrounding the probe, called a flux-tube, can form for a probe size comparable with or larger than the electron Larmor radius. The formation of the flux-tube strongly affects the components of the laser photo-detachment signal, leading to an important oscillation of probe current during the plateau phase, i.e. the amplitude of the AC component of the probe current is in the same magnitude order of the DC component of this current, and an important overshoot in comparison to the current rise. Numerical results are qualitatively compared to measurements obtained from the RAID negative ion source.